PENGARUH HARGA DAN INOVASI PRODUK TERHADAP MINAT BELI KONSUMEN PADA PT INDACO WARNA DUNIA DI KOTA BATAM - Wahid, Abdul; Santoso, Teguh Iman (SCIENTIA JOURNAL, 2019)
The company's success is determined by a strategy that is adjusted to the situation and conditions of the target market. Companies are required to implement a wise marketing strategy by analyzing the situation and target market, setting the right marketing goals, and designing marketing strategies that can adapt to increasingly competitive business situations. All of these policies will help the company to achieve the targets. This study aims to determine the role of prices and product innovation in increasing consumer buying interest in PT. Indaco Warna Dunia on Batam city. Using multiple linear analysis, T test to determine the effect partially, F test to determine the effect simultaneously, R Test to find out how strong the influence of independent variables on the dependent variable. Processing data using SPSS 16. The results of this study are that prices have a significant effect on consumer buying interest. Product innovation has a significant effect on consumer buying interest. Together, price and product innovation have a significant effect on consumers' buying interest.